Age- and Sex-Dependent Modulation of Exogenous Ketone Supplement-Evoked Effects on Blood Glucose and Ketone Body Levels in Wistar Albino Glaxo Rijswijk Rats - Kovács, Zsolt; Brunner, Brigitta; D’Agostino, Dominic P.; Ari, Csilla (Frontiers in Neuroscience, 2021)
In certain disease states, such as epilepsy, the elevation of blood ketone levels with ketogenic diets (KDs) has beneficial effects, while exogenous ketone supplements (EKSs) were shown to increase the level of blood ketone bodies (such as β-hydroxybutyrate, βHB) and decrease blood glucose levels without dietary restrictions. It has been suggested that ketone body and glucose utilization of the body may be modified by age and gender resulting changes in blood βHB and glucose levels, but it was not investigated through several months yet. Thus, we investigated whether the effect of an EKS on blood βHB and glucose level is modulated by age and sex in Wistar Albino Glaxo Rijswijk (WAG/Rij) rats, a model animal of human absence epilepsy. We used KEMCT (1:1 mix of ketone ester/KE and medium chain triglyceride/MCT oil) by oral gavage in female and male WAG/Rij rats. Animals were fed with standard diet, which was supplemented by KEMCT (2.5 g/kg) once per month by oral gavage for 17 months. One hour after KEMCT treatment, changes in blood R-βHB and glucose levels were measured. KEMCT gavage significantly increased blood R-βHB and decreased blood glucose levels, in both male and female rats, compared to controls. In male rats, the KEMCT-induced increase in blood R-βHB levels was lower at 7th and 8th months, and higher at 16th and 17th months, compared to results at 1st month. KEMCT-generated increase in R-βHB levels was higher in female rats, compared to male rats between 2nd and 11th month, but older (between 14th and 17th month) female rats showed lower levels than males. KEMCT gavage induced significantly lower glucose levels at 4th, 9th, 10th, 12th and 13th months in both sexes, but between 14th and 17th months only males showed significantly lower levels, compared to results at 1st month. KEMCT treatment induced lower blood glucose levels in female than in male rats between 1st and 8th months, but higher glucose levels were measured in female rats at 17th month than in males. These findings suggest that age and sex can modify the EKSs-evoked effects on blood R-βHB and glucose concentrations.